Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_807_816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Time Dependent Fatigue Crack Growth Behavior in a P/M Turbine Disk Alloy

Abstract: A study was conducted to determine the processes which govern hold time crack growth behavior in the LSHR disk P/M superalloy. Nineteen different heat treatments of this alloy were evaluated by systematically controlling the cooling rate from the supersolvus solutioning step and applying various single and double step aging treatments. The resulting hold time crack growth rates varied by more than two orders of magnitude. It was shown that the associated stress relaxation behavior for these heat treatments was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 10 publications
5
48
1
Order By: Relevance
“…Once the yield strength reaches a sufficiently large value, approximately 1150 MPa in this alloy studied here, the excessive pinning of the grain boundary results in apparent grain boundary embrittlement and a decrease in stress relaxation leading to higher crack growth rate. This second trend for  y > 1150 MPa, is in agreement with results of Telesman et al [10] which suggest that an increased stress relaxation at the crack tip corresponds to a lower crack growth rate.…”
Section: (A)supporting
confidence: 81%
“…Once the yield strength reaches a sufficiently large value, approximately 1150 MPa in this alloy studied here, the excessive pinning of the grain boundary results in apparent grain boundary embrittlement and a decrease in stress relaxation leading to higher crack growth rate. This second trend for  y > 1150 MPa, is in agreement with results of Telesman et al [10] which suggest that an increased stress relaxation at the crack tip corresponds to a lower crack growth rate.…”
Section: (A)supporting
confidence: 81%
“…The formation of different constituents of oxides was confirmed and ultimately observed to dictate different crack growth behaviour in an advanced RR1000 nickel disc alloy [7]. However, it is suggested that it is the kinetics of crack tip stress relaxation that plays a significant role on the constituent and the rupture of oxide intrusions ahead of the crack tip [1,7]. It is also likely that crack growth behaviour is extremely sensitive to microstructure variations with a reduction of external stress intensity factor towards the time dependent threshold value [7].…”
Section: Introductionmentioning
confidence: 94%
“…At high temperature in air, introducing a dwell period into fatigue cycles can cause cyclic crack growth rates to increase in nickel based superalloys, associated with a change of crack morphology from transgranular to intergranular [1]. Compared to traditional disc alloys, modern nickel based superalloys have higher yield strength and creep resistance to meet the requirement of improved performance and fuel efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[41] It has been reported that the dwell fatigue performance of Ni-base superalloys can be improved by increasing Cr content, [89,90] volume fraction of c¢, [89] and the size of tertiary c¢ precipitates. [41,91,92] The improvements by increasing Cr content and tertiary c¢ size are qualitatively illustrated in Figure 10(a). One possible explanation for these microstructural and alloying effects may be the increase in transformation toughening and the K th value by increasing Cr contents on the basis that increasing the Cr content of the Ni-base alloy is likely to promote the formation of Cr 2 O 3 .…”
Section: ½20mentioning
confidence: 71%
“…One possible explanation for these microstructural and alloying effects may be the increase in transformation toughening and the K th value by increasing Cr contents on the basis that increasing the Cr content of the Ni-base alloy is likely to promote the formation of Cr 2 O 3 . Similarly, increasing the tertiary c¢ size is likely to promote stress relaxation at the cracktip, [91,92] which would delay fracture of the oxide and increase the apparent K th . In addition, the larger tertiary c¢ size may also promote the formation of Al 2 O 3 by Al from tertiary Ni 3 Al at or near grain boundaries.…”
Section: ½20mentioning
confidence: 99%